Evaluation of 3d environments and virtual realities in science teaching and learning: The need to go beyond perception referents - Oloruntegbe, K.O.; Alam, G.M. (2010)
There is a raging debate in literature about the effectiveness of 3D environments and virtual realities. The debate seems an unending one with both the advocates and critiques striving to justify their various positions. A survey of literature, however, revealed the absence of sufficient data to justify taking a position. This led the authors to hypothesize that most of the evaluation carried out in this area did go beyond perception referents. Over one thousand articles in reputable journals and proceedings were consulted including a few others without affiliation. Twenty four that covered the amorphous subjects of evaluation, assessment, effectiveness, potentials and benefits were painstakingly analyzed for their coverage particularly over the three leaning outcomes of cognitive, skills and attitudes. The findings revealed that while there were evidences of learning improvement and performance enhancement, over eighty five percent of the data revolved around affective dispositions of satisfaction, interest, enjoyment and fun. With this, the authors concluded that there was no sufficient evidence yet to back up the pedagogical effectiveness of this state-of-art technology. The authors, however, appreciates the newness of this field of human endeavour, and is of the opinion that sufficient time, spread and focus are required to make valid evaluation possible.